Response Advantage for the Identification of Speech Sounds - Moskowitz, Howard S.; Lee, Wei Wei; Sussman, Elyse S. (Frontiers in Psychology, 2020)
The ability to distinguish among different types of sounds in the environment and to identify sound sources is a fundamental skill of the auditory system. This study tested responses to sounds by stimulus category (speech, music, and environmental) in adults with normal hearing to determine under what task conditions there was a processing advantage for speech. We hypothesized that speech sounds would be processed faster and more accurately than non-speech sounds under specific listening conditions and different behavioral goals. Thus, we used three different task conditions allowing us to compare detection and identification of sound categories in an auditory oddball paradigm and in a repetition-switch category paradigm. We found that response time and accuracy were modulated by the specific task demands. The sound category itself had no effect on sound detection outcomes but had a pronounced effect on sound identification. Faster and more accurate responses to speech were found only when identifying sounds. We demonstrate a speech processing “advantage” when identifying the sound category among non-categorical sounds and when detecting and identifying among categorical sounds. Thus, overall, our results are consistent with a theory of speech processing that relies on specialized systems distinct from music and other environmental sounds.